Whole-genome sequencing based molecular characterization of multi-drug resistant isolates of Enterobacter spp. and Klebsiella aerogenes in Lebanon. (c2019) - Merhi, Georgi S. (2019)
Enterobacter cloacae complex (ECC) members and Klebsiella aerogenes belong to the family Enterobacteriaceae and are known as Gram-negative, rod-shaped, opportunistic pathogens. They are commonly notorious for causing healthcare-associated infections and impose a significant burden on secondary health-centers. In the last few decades, the rise of ECC and K. aerogenes as successful nosocomial pathogens was paralleled by the global alarming emergence of multi-drug resistant clones of these bacteria. In Lebanon only few sporadic, and somewhat lacking, reports exist on multi-drug resistant ECC and K. aerogenes isolates. In our study whole-genome sequencing (WGS) was used for the molecular characterization of 15 E. cloacae complex and K. aerogenes recovered from clinical settings. The isolates were initially collected and characterized through hsp60 genotyping and 16S rRNA gene sequencing. Pulse field gel electrophoresis (PFGE) and multi-locus sequence typing (MLST) were used to investigate the clonal relatedness and antimicrobial susceptibility was tested and confirmed through in silico analysis. Results were further confirmed through complimentary PCR assays and plasmid-based replicon typing (PBRT). Phylogenetic relatedness was assessed through whole-genome average nucleotide identity (wgANI) and core-genome single nucleotide polymorphism (cgSNP) based phylogenetic analysis. Eight isolates were identified as Enterobacter hormaechei (clusters III, VI, VIII) representing 88% (n=8) of the total studied Enterobacter isolates. 53% (n=8) of isolates exhibited resistance to one or more of the tested penicillin and cephalosporins, while only 20% (n=3) showed complete resistance to carbapenems. Novel STs were determined for ECC and K. aerogenes isolates and one ECC isolate (ST114) matched an epidemic clone. IncFII plasmids were detected in 47% (n=7) of the isolates, which conforms with the most common plasmid families in both ECC and K. aerogenes. One blaCTX-M-15 positive ECC isolate had the ESBL gene integrated in the chromosome through an ISEcp1-blaCTX-M-15-orf477Δ transposition unit, while a second extremely resistant ECC isolate coharbored blaNDM-1 and blaCTX-M-15. Carbapenem resistance in K. aerogenes isolates was due to the additive effect of osmoporin inactivation (omp36) and constitutive chromosomal ampC expression. The results of this study showed the polyphyletic nature of the ECC and its dissemination in Lebanon and revealed its resistance mechanisms. The generated data could be used for other comparative genomic studies to better understand the molecular epidemiology, the dynamics of dissemination and the genetic basis of multidrug resistance within nosocomial pathogens in Lebanon.